Design and Evaluation of Formulated Mouth Dissolving Film of Domperidone and Study the Effect of Concentration of Polymers on Drug Release - Chougule, Pankaj C. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: One of the important aspects of medication, which are depending on the basis of drug release and bioavailability. Orally fast dissolving film is a new drug delivery system designed for the oral delivery of the drugs and developed on the basis of technology of the transdermal patch. Materials and Methods: Designed thin mouth dissolving film of domperidone with polyvinyl alcohol (PVA) as a water-soluble polymer and polyethylene glycol 400 as a plasticizer was prepared by solvent casting method. Fourier-transform infrared study was conducted for drug-polymer interaction and formulation. Results and Discussion: The designed films were evaluated for mechanical properties and in vitro dissolution test, including drug-polymer interaction study. Stability study was conducted for physical stability and in vitro drug release. Conclusion: It was observed that drug release was decreased as the concentration of polymer increases. The various parameters were studied such as the effect of concentration of PVA and effect of plasticizers on film properties. The high % drug release of the film in 6.8 pH phosphate buffer indicated that it could be helpful for the treatment of common cold, rhinitis, where quick bioavailability of drug is desired.